Analisis Miskonsepsi Siswa Kelas VI Sekolah Dasar pada Konsep Sistem Gerak Manusia melalui Metode Four-Tier Diagnostic Test - Ika Isna Umiyati; Fina Fakhriyah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2026)
Misconceptions are understandings that do not conform to scientifically accepted concepts, but are believed to be true by students. Misconceptions in elementary school students tend to be resistant and difficult to change if not identified early. This study aims to analyze the misconceptions of sixth grade elementary school students on the material of the human movement system. This material is often considered complex because it involves the relationship between bones, joints, muscles, and the health of the movement system. The type of research used is quantitative with a survey design. The research subjects consisted of 19 sixth grade students of SD Negeri Growong Kidul 02 who were selected through a total sampling technique. The research instrument was 10 diagnostic test items in a four-tier format (four levels) which included the level of answer, answer confidence, reasons, and reason confidence. The results showed that students' conceptual understanding was divided into three main categories: Concept Understanding (PK) of 48.42%, Misconception (M) of 50.53%, and Lack of Understanding (KP) of 1.05%. These findings indicate that misconceptions outweigh students' conceptual understanding, particularly regarding the mechanisms of antagonistic and synergistic muscles, the function and types of joints, and the relationship between nutrition and bone health. The use of a four-tier diagnostic test proved effective in accurately distinguishing students with a true understanding from those with misconceptions. This study concludes the need for innovative learning strategies and the use of concrete media to minimize misconceptions so that students have a strong foundation of scientific knowledge for the next level of education.